An enigmatic group of arctic island caribou and the potential implications for conservation of biodiversity - McFarlane, Keri; Miller, Frank L.; Barry, Samuel J.; Wilson, Gregory A. (Rangifer, 2014)
We investigated the status of caribou classified as Rangifer tarandus pearyi by DNA analyses, with an emphasis on those large-bodied caribou identified as ultra pearyi that were collected in summer 1958 on Prince of Wales Island, south-central Canadian Arctic Archipelago. Our comparative assessment reveals that the ultra pearyi from Prince of Wales Island belong to a group of pearyi and are not hybrids of pearyi x groenlandicus, as we found for the caribou occurring on nearby Banks Island and northwest Victoria Island. The ultra pearyi from Prince of Wales Island cluster with high arctic pearyi and are separated genetically from the caribou populations that we sampled on the low Canadian Arctic Islands and the Canadian mainland. Our findings reveal biodiversity below the level of subspecies or regional designations. These results support the position that to retain the biodiversity present among caribou populations on the Canadian Arctic Islands, conservation efforts should be targeted at the smaller scale level of the geographic population, rather than on a wider regional or subspecific range-wide basis.